Factors Associated with Health Personnel Performance in Tuberculosis Control Using - Reni Dwi Pangestuti; Sri Hernawati; Farida Wahyu Ningtyias (Journal of Health Policy and Management, 2018)
Background: Tuberculosis (TB) remains a major public health problem in the world that causes morbidity and mortality. The role of health personnel is important in the implementation of lung TB control program. Health personnel performance that is not optimal can cause the TB case to remain high. Little is known about the factors affecting the performance of health personnel in Indonesia. This study aimed to examinethe determinants of health personnel performance in TB control using